Determination of 5‐Formyluracil via Oxime‐Based Nucleotide‐Metal Coordination. (28th July 2022) - Zhang, Kaiyuan; Fu, Boshi; Zou, Guangrong; Yang, Wei; Yan, Shen; Tian, Tian; Zhou, Xiang
Abstract: 2‐(Aminooxy)‐ N ‐(quinolin‐8‐yl)acetamide was synthesized, and its ability to regulate activities of DNA polymerase was tested. In addition, we used the isothermal amplification technology to detect the content of 5‐formyluracil sites in irradiated genomic DNA, which confirmed its capability for the detection of 5‐formyluracil content in general samples. This study presents the first example of the determination of 5fU based on coordination chemistry. Abstract : After its reaction with 5‐formyluracil, a small chemical molecule, 2‐(aminooxy)‐ N ‐(quinolin‐8‐yl)acetamide, was used to regulate activities of DNA polymerase. Then, the content of 5‐formyluracil sites in DNA samples was detected by isothermal amplification strategy. According to the calculation of experimental data, 14.7 5‐formyluracil components per 10 6 nucleotides per Gy were obtained in the radiation process.